Low cost spectro photometric determination of paraquat in environmental and biological sample - Khatoon, R; Rai, M K; Rai, J K (Recent Research in Science and Technology, 2013)
An extractive, sensitive spectrophotometer method has been developed for the detection and determination of paraquat using glucose ( as easily available reducing agent ). Paraquat is reduced with glucose in alkaline medium to give a blue colored ion with an absorbance maxima at 610 nm. Beer’s law is obeyed in the range 0.5-5.0 µg of paraquat in 10ml of the final solution (ppm). The important analytical parameters and the optimum reaction conditions were evaluated. The method was applied successfully to the determination of paraquat in water, grain, plant material and biological sample.